EPIGENETIC BASIS FOR ABDOMINAL AORTIC VASCULAR SMOOTH MUSCLE ADAPTATION TO PREGNANCY - Gelinne, Aaron (J Vasc Res, 2018)
BACKGROUND/AIMS: Ten-Eleven-Translocation (Tet), a DNA demethylase enzyme, has been identified as a master epigenetic regulator of vascular smooth muscle cell plasticity that could alter the biomechanics of the pregnant aorta. We hypothesized that pregnancy will induce significant adaptive changes in aortic caliber and distensibility that correlate to Tet gene expression. METHODS: Abdominal aortas from pregnant and non-pregnant mice were dissected and cannulated. Intraluminal pressure was adjusted using a pressure-servo system while using a video dimension analyzer to measure lumen diameter. qPCR and immunoblot was used to analyze expression of Tet genes. Global genomic methylation was assessed with the LUMA assay. RESULTS: Compared to the NP (706 ± 8 μm) control group, aortic luminal diameter was significantly increased in both E18.5 (836 ± 14 μm) and PP30 (889 ± 16 μm) mice. Distensibility was reduced in E18.5 (90 ± 4%) mice and returned to NP (108 ± 2%) values in PP30 (108 ± 3%) mice. Tet2 transcription decreased in the beginning of pregnancy and subsequently increased in late gestation; inversely corresponding to changes in global methylation. CONCLUSIONS: Physiologic changes in the aorta are accompanied by changes in gene expression and genomic methylation, suggesting an epigenetic component to maternal vascular remodeling during pregnancy.